EDUCAÇÃO AMBIENTAL EM UNIDADES DE CONSERVAÇÃO: TOUR VIRTUAL SOCIOAMBIENTAL COMO ESTRATÉGIA DE ENSINO - Luz, Carlos Henrique Gonçalves (2021)
The critical Environmental Education (EE) seeks to transform human actions in the face of the current socio-environmental crisis, by promoting reflections and educational actions on contemporary challenges and dilemmas, and through a social practice that enables a (re)signification of the reading of people’s worlds. Conservation Units (CU) are natural areas protected by law in Brazil, which can act as places and mediation strategies for existing socioenvironmental conflicts in our country. Through interdisciplinary and transversal actions, focused on understanding and transforming social practice and on the search for a critical and meaningful learning, we can elaborate different teaching materials that can contribute to the teaching and learning process that take place both in formal and non-formal environments of education. Due to the current COVID-19 Pandemic moment, education and teaching processes have undergone a drastic change in the way is taught and learned and the utilization of technologies has become a part of the lives of teachers and students. Given this context, both emancipation and educational transformation need to be broad, not only in the technological sense, but also in relation to the human side, which can contribute to a critical reflection of people in relation to the socio-environmental challenges experienced and in the correct utilization of technology tools for teaching. Thus, in this research, we sought to developed and evaluated a didactic instrument, more precisely a 360º Virtual Reality (VR) tour, which is made of cardboard glasses and aims to promote virtual immersions in CUs, based on images from the Felippe Paulo Rickli Ecological Station from the City of Turvo – PR. The validation of the virtual tour was carried out using the Likert scale by the NEA (Environmental Education Group) study group of the Universidade Estadual do Centro Oeste and with public school teachers from Turvo - PR. For its evaluation, a focus group was created with the same teachers, who verified the need for changes on the product, as well as evaluated it as a promising instrument for the discussion of social and environmental problems experienced by communities in small cities, such as Turvo - PR, which its main economy is focused on agriculture, and which possesses protected areas destined for preservation. The tour proved to be a didactic and pedagogical instrument capable of working with critical EE in both formal and non-formal environments, assisting on bringing teachers from different areas of knowledge together and on the utilization of new technologies in teaching. In addition, this instrument also caused the approximation between the principles of EE, Meaningful Learning and Conservation Biology, because when practicing EE in its social, cultural, political, economic, and environmental context, associated with the formation of transforming and critical beings, in the face of contemporary social situations, we are inducing the emancipation of active and critical subjects in our society.